Logistics Distribution Optimization Model Using the Hub and Spoke Method Based on Distribution Requirement Planning: A Case Study of the Indonesian Navy’s Koarmada I - Wisnu Utomo; Aries Sudiarso; Sri Yanto (Indonesian Journal of Advanced Research, 2026)
Logistics distribution plays a strategic role in supporting the operational readiness of the Indonesian Navy, particularly in the Koarmada I area, which has archipelagic characteristics and widely dispersed destination units. The existing distribution system still relies on the Central Depot in Jakarta and depends on the availability of operational transport modes. This condition affects distribution distance, travel time, lead time, and distribution cost. This study aims to design an optimized logistics distribution model using the Hub and Spoke method based on Distribution Requirement Planning (DRP). The study applies a quantitative case study approach through existing condition analysis, hub location determination using the Center of Gravity (CoG) method, QGIS-based spatial visualization, aggregate efficiency analysis, and quarterly DRP simulation. The results show that Batam is more feasible as a distribution hub than Tanjung Pinang. The proposed Batam Hub model reduces aggregate distribution distance from 2,445 Nm to 2,140 Nm, travel time from 244.5 hours to 214 hours, and distribution cost from IDR 4,198,920,750 to IDR 3,675,129,000. These reductions represent an aggregate efficiency of 12.5% across distance, time, and cost indicators. In addition, DRP supports more structured planning of Kaporlap logistics requirements based on quarterly distribution periods. Therefore, the Hub and Spoke model integrated with DRP can serve as an alternative logistics distribution model that is more efficient, structured, and supportive of Koarmada I operational readiness. To maintain information security, coordinates, actual operational routes, technical parameters, and detailed route-based calculations are not presented in this article.